Pure Polyurethane and Castor Oil Based Polyurethane: Synthesis and Characterization - M. A., Alaa; K., Yusoh; S. F., Hasany (Faculty Mechanical Engineering, UMP, 2015)
In this study, the physico-chemical properties of high performance polyurethane synthesized from poly propylene glycol (PPG) in comparison with a combination of PPG and castor oil, is studied using the in-situ polymerization technique. The variations in properties of both types of polyurethanes are evaluated by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD) and the thermogravimetric analysis (TGA) technique. Tensile strength properties were investigated by film tensile testing equipment. The results indicated the presence of large -CH stretching in the castor oil mixed polyurethane with a larger oxidative thermal stability over pure PPG polyurethanes. The tensile properties were found to be almost comparable in pure and mixed polymers, signifying the usage of mixed polymers in the future to overcome the environmental and economic crisis in polyurethane synthesis